The Effects of Socioeconomic Determinants on Hypertension in a Cardiometabolic At-Risk European Country. (28th August 2017) - Cuschieri, Sarah; Vassallo, Josanne; Calleja, Neville; Pace, Nikolai; Mamo, Julian
Abstract : Background. A relationship has been established between socioeconomic status and hypertension. The aim of this study was to determine the prevalence of hypertension and to explore the links between hypertension and socioeconomic factors in the adult population of Malta. Methods. A national representative cross-sectional health examination study was performed between 2014 and 2016. Sociodemographic and medical history data was gathered by validated questionnaires while blood pressure was measured. Prevalence rates of known hypertension, newly hypertension, and global hypertension were calculated. Associations between sociodemographic characteristics and hypertension were identified through logistic regression models. Results. Hypertension contributed to 30.12% (CI 95%: 28.71–31.57) of the study population, with a male preponderance. The majority was known hypertensive (73.59% CI 95%: 71.01–76.02), with only three-quarters on medication. Multivariant analyses showed that increasing age and body mass index, male gender, and living in Gozo, Western district, and Northern Harbour district were associated with having hypertension. Conclusion. Hypertension is a problem in Malta especially in the male population and with increasing age and body mass index. Education did not exhibit any associated risk for having hypertension, which is inconsistent with the literature, while habitat localities played a role in hypertension development.